Methodology for determining the parameters of the air flow in a pneumatic separator with a closed air system - Mykhailov, Yevhen; Михайлов, Євген Володимирович; Михайлов, Евгений Владимирович; Zadosnaia, Nadya; Kangalov, Plamen; Mykhaylov, Yevhen (Tavria state agrotechnological university, 2017)
The paper considers the state of grain materials coming from grain harvesters for preliminary cleaning. Preliminary cleaning of grain is to separate large and air-separated impurities from the grain and thereby improve their flowability. This increases their safety during temporary storage. Pre-cleaning is necessary for seed and all food grain after harvesting. The analysis of work of software tools and methods of their research is conducted. To a lesser extent, studies on the procedure for determining the parameters and operating modes of the scalper type air separator are presented, which determines the relevance of the study. The device and the technological process of operation of a pneumatic separator with a closed air system are proposed, which pushes the task of developing a methodology for their investigation. A special novelty in the study of airflow parameters of a pneumatic separator is a two-stage sedimentary chamber and a suction channel of the fan, which influence the validation of airflow parameters in the zone of fluidization of grain materials (ZM) and their pneumoseparation. An important role in this determines the injection airflow, which diametrically permeates a cylindrical sieve. The state of the air flow structure and the analysis of factors ensuring the quality of cleaning grain material, constitute the main task of the study of the pneumatic separator. A procedure for determining the airflow parameters of a scalper-type air separator is developed by studying the structure and air speed diagrams in the sections of the air distributor, the pneumatic separating and sedimentation chambers. The structure and air speed diagrams in the air distributor are studied in five sections. The values of dynamic pressure and air flow are determined. When changing the live cross-section of the air distributor, different values of the angles of inclination of the middle moving and rear moving walls and the coefficient of the live section of the intensifier tray are taken into account. Based on the obtained data, the working airflow rates are determined, the velocity diagrams are constructed, the structure hydraulic resistance of the pneumatic system is formed. This allows making adjustments to the definition of rational and optimal values of the parameters and modes of operation of pneumatic system. The result is increasing the efficiency of pneumoseparation and reduction of its energy consumption.
Keywords: pneumoseparation; grain; airflow; lots of grain; light impurities; dust